Rohingya Refugee Crisis in Bangladesh: The Case of UNHCR’s Response - Taufiq -E- Faruque (Universitas Muhammadiyah Yogyakarta, 2020)
How does the Office of the United Nations High Commissioner for Refugees (UNHCR) respond to a sudden influx of a large number of refugees in a state rejecting the international legal standards on refugee protection? By applying a qualitative case study method, this article seeks to shed light on that question by focusing on the UNHCR’s response in the context of the Rohingya refugee influx to Bangladesh, a non-signatory state to the 1951 Refugee Convention and its 1967. This article recognizes the existence regime complexity involving the international refugee regime and argues that Bangladesh has tried to challenge UNHCR’s involvement through authorizing the International Organization for Migration (IOM) to lead the international humanitarian response in the early days of the 2017-18 Rohingya refugee crisis. Furthermore, this article adopts challenged institutions as a framework to explore how the UNHCR responded to the challenge through a series of strategic maneuvers to uphold its mandate of providing “international protection” to the Rohingya refugees in Bangladesh. The main findings suggested that although UNHCR has been able to emerge as a leading stakeholder of the humanitarian response to the Rohingya refugee crisis, the existing operational context in Bangladesh still challenges the agency to uphold its mandate fully. Other findings include the fragmentation of authority in the international response coordination, increasing institutional competition, and lack of coordination between UNHCR and other major humanitarian agencies.